Creating infrastructure for seismic microzonation by Geographical Information Systems (GIS): A case study in the North Anatolian Fault Zone (NAFZ) - Turk, T.; Gumusay, U.; Tatar, O. (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Although there are many studies for seismic microzonation in the literature, these studies have not covered the whole seismic microzonation processes. Moreover, they have not sufficiently focused on the important subjects, such as significance and use of aerial photos in seismic microzonation studies, data types used for seismic microzonation, and integrating these data by GIS. This study suggests a GIS-based model that can be used for all settlements that are at risk of natural disaster, with a view to taking necessary measures against such natural disasters (especially earthquakes). This model was applied so as to take the measures needed for the town of Erbaa located on the western part of the eastern segments of the North Anatolian Fault Zone (NAFZ), a settlement with earthquake risk on the NAFZ. During creation of the system, geological, geotechnical data and data produced from aerial photos were integrated and assessed on a GIS environment The infrastructure for seismic microzonation was created using this model. The potential areas for soil liquefaction were detected in the study area. Thus, the results were produced to assist in seismic microzonation. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: GIS; North Anatolian Fault Zone; Photogrammetry; Seismic microzonation; Spatiotemporal analysis; LANDSLIDE SUSCEPTIBILITY; EARTHQUAKE; HAZARD; TOOL; IMAGES; MODEL; RISK; Computer Science; Geology